Improving Student Learning Outcomes Through The Development Of Videoscribe Sparkol-Based Learning Media - Abdul Wahid Zaini; Samsul Susilawati; Rini Nafsiati Astuti (Institut Agama Islam An-Nawawi Purworejo, 2022)
The objectives of this research and development are; 1) To determine the feasibility of Sparkol Videoscribe-based video learning media, 2) To explain the attractiveness of Sparkol Videoscribe-based video learning media, 3) to test the effectiveness of using Sparkol Videoscribe-based video learning media. This type of development research is Research and Development (R&D), which refers to the Borg & Gall model. The subjects in this study were fourth-grade students at MI Miftahul Ulum Pandan Wangi. Data collection techniques in this study used interviews, achievement tests, and questionnaires. The data analysis technique used is qualitative and quantitative analysis techniques. The research was conducted at MI Mifatahul Ulum Pandanwangi with test subjects of 25 students in class IV A and 25 students in class IV B. The research results on developing video learning media based on Sparkol Videoscribe met the valid criteria, with material experts reaching a validity level of 97.5%, design experts at 97.5%, and learning practitioners at 95%. In the post-test analysis for the experimental class, the result was 85.04, while for the control class, it was 70.28. In the t-test obtained at t-count 3.55 and t-table 2.06. From these data, it can be concluded that the t table is larger than the t count, so the results are significant, with Ha being accepted and Ho rejecting. So that Sparkol Videoscribe learning media effectively improves student learning outcomes in the life cycle material of living things in class IV students.